2014
DOI: 10.1186/1472-6882-14-327
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and anticancer activity of Darjeeling tea in multiple test systems

Abstract: BackgroundDarjeeling tea, a most popular variety of black tea, though consumed by the people in different parts of world but its beneficial health effects have not been investigated in details. In this study, the antimutagenic and anticancer effect of Darjeeling tea extract (DTE) has been evaluated.MethodsAntimutagenic activity of the DTE was carried out in two different strains of Salmonella typhimurium by AMES test against a known mutagen benzo[a]pyrene (B[a]P) with S9 activation. Moreover, anticlastogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Tea leaves can be processed into the most widely consumed beverage. Increasing evidence suggests that tea extracts produce beneficial health effects, such as anticancer [ 2 ], anti-vascular disease [ 3 ], anti-bacterial [ 4 ], anti-inflammation [ 5 ], and anti-allergic [ 6 ] activities. The leaves of tea plants have large amounts of flavonoids, which include flavones, flavanones, flavonols, flavan 3-ols (as known as catechins), and anthocyanidins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tea leaves can be processed into the most widely consumed beverage. Increasing evidence suggests that tea extracts produce beneficial health effects, such as anticancer [ 2 ], anti-vascular disease [ 3 ], anti-bacterial [ 4 ], anti-inflammation [ 5 ], and anti-allergic [ 6 ] activities. The leaves of tea plants have large amounts of flavonoids, which include flavones, flavanones, flavonols, flavan 3-ols (as known as catechins), and anthocyanidins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, a growing number of studies have identified different plants extracts with antigenotoxic potential, such as: Mentha longifolia (Al-Ali et al 2014), Dioscorea pentaphylla (Prakash et al 2014), Lilium candidum (Jovtchev et al 2014), Eucalyptus Gunnii (Bugarin et al 2014), Camellia sinensis (Bhattacharya et al 2014), Curcuma longa (Liju et al 2014), Celtis iguanaea (Borges et al 2013), Solanum paniculatum (Vieira et al 2013), Synadenium umbellatum (Melo-Reis et al 2011), Ginkgo biloba (Vilar et al 2009), and others. Thus, there has been growing interest in finding and using natural plant products to reduce genotoxic and/or carcinogenic effects.…”
Section: Introductionmentioning
confidence: 99%